Schrödinger operators with nonlocal potentials - Nizhnik, L. P.; Albeverio, S. (Methods of Functional Analysis and Topology, 2013)
We describe selfadjoint nonlocal boundary-value conditions for new exact solvable models of Schrödinger operators with nonlocal potentials. We also solve the direct and the inverse spectral problems on a bounded line segment, as well as the scattering problem on the whole axis for first order operators with a nonlocal potential.